2019
DOI: 10.18325/jkmr.2019.29.4.61
|View full text |Cite
|
Sign up to set email alerts
|

Trend of Disabled Person Care for Establishment of Visiting Health Management Model for the Disabled

Abstract: Objectives We analyzed and organized present studies related to medical care for the disabled to establish an appropriate model of visiting health management for the people with disability. Methods To analyse study of medical care for the disabled, 11 electonic databases (PubMed, Chinese Academic Journals, EMBASE, Cochrane Library, Medline, Oasis, KMBASE, KISS, KISTI, NDSL, RISS) were searched from 2009 to 2018. There's no limit to the type of study. Results The search showed 20 domestic studies and 113 foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…4 A study by Kim et al showed that medical professionals, who are the main providers of services for people with disabilities, tended to have negative attitudes toward people with disabilities. 5 However, the more experienced these professionals in working or building relationships with these people, the more positive their attitudes toward them. 2,4 This allows us to suggest that greater experience and familiarity with disability leads to more positive attitudes toward people with disabilities among health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…4 A study by Kim et al showed that medical professionals, who are the main providers of services for people with disabilities, tended to have negative attitudes toward people with disabilities. 5 However, the more experienced these professionals in working or building relationships with these people, the more positive their attitudes toward them. 2,4 This allows us to suggest that greater experience and familiarity with disability leads to more positive attitudes toward people with disabilities among health care professionals.…”
Section: Introductionmentioning
confidence: 99%